Current Medical Treatments for Juvenile Idiopathic Arthritis - Martini, Alberto; Ruperto, Nicolino (Frontiers in Pharmacology, 2011)
Juvenile idiopathic arthritis (JIA) differs markedly from adult rheumatoid arthritis. It is not a single disease, but an exclusion diagnosis that gather together all forms of arthritis that begin before the age of 16 years, persist for more than 6 weeks, and are of unknown origin. The advent of the new biological treatments has dramatically changed both the observed responses to treatment and the expectations of therapies. The implementation of an adequate legislation as well as the presence of international research networks of pediatric rheumatology have contributed to foster the conduct of controlled clinical trials and the development of validated outcome measures. This review will currently describe the methodological approach for performing clinical trials in JIA as well as the current available drug treatment.